Opposing role of phagocytic receptors MERTK and AXL in Progranulin deficient FTD - Claire Dudley Clelland; Li Fan; Rowan Saloner; Jon Iker Etchegaray; Chad Richard Altobelli; Sally Salomonsson; Alisha M. Maltos; Aradhana Sachdev; Jingjie Zhu; Se-In Lee; Yaqiao Li; Yungui Zhou; et al. (Communications Biology)
Abstract Genetic mutations in the progranulin gene, GRN, cause frontotemporal dementia and a lysosomal storage disorder. Using single-nuclei RNA sequencing of the post-mortem brain tissue from adult heterozygous pathogenic granulin variant (GRN+/−) carriers we find dysregulation of microglia, phagocytosis and the phagocytic receptors MERTK and AXL. Exogenous progranulin regulates MERTK and AXL RNA expression in human microglia induced from iPSCs irrespective of GRN mutation status, without directly binding to MERTK or AXL proteins. We generated double knock-out mice and find that constitutive homozygous loss of Grn and Mertk (Grn−/−;Mertk−/−) rescued microglial disease signature while constitutive homozygous loss of Grn and Axl (Grn−/−;Axl−/−) worsened the microglial disease signature and increased lipofuscin. Lower CSF MERTK but not AXL is associated with lower progranulin levels. Furthermore, CSF MERTK is lower in symptomatic but not presymptomatic FTD patients with genetic mutations (GRN, C9ORF72, and MAPT) whereas AXL does not change between disease state and control. These data explain in part the inflammation seen in GRN-FTD and are applicable to other inflammatory states in which PGRN, MERTK and AXL play regulatory roles beyond neurodegenerative diseases. The interaction between GRN, MERTK, and AXL opens potential new therapeutic avenues to intervene on this inflammatory axis.